Jake Drake, teacher's pet - Clements, Andrew, 1949-; Frazee, Marla; Pedersen, Janet (New York : Scholastic Inc., 2008)
Jake doesn't mean to be a teacher's pet. But somehow everything he does has his teachers singing his praises -- and his classmates rolling their eyes in disgust. Jake figures a little misbehavior should take care of his goody-goody image, but even his attempts to be bad just seem to make his teacher's praise him more. And now he's been summoned to the principal's office. Has Jake gone too far to prove he's no teacher's pet?
Keywords: Drake, Jake (Fictitious character) -- Juvenile fiction; Teacher-student relationships -- Juvenile fiction; Schools -- Juvenile fiction; Teacher-student relationships -- Fiction; Schools -- Fiction